2021
DOI: 10.1371/journal.pone.0249350
|View full text |Cite
|
Sign up to set email alerts
|

A p53-like transcription factor, BbTFO1, contributes to virulence and oxidative and thermal stress tolerances in the insect pathogenic fungus, Beauveria bassiana

Abstract: The p53-like transcription factor (TF) NDT80 plays a vital role in the regulation of pathogenic mechanisms and meiosis in certain fungi. However, the effects of NDT80 on entomopathogenic fungi are still unknown. In this paper, the NDT80 orthologue BbTFO1 was examined in Beauveria bassiana, a filamentous entomopathogenic fungus, to explore the role of an NDT80-like protein for fungal pest control potential. Disruption of BbTFO1 resulted in impaired resistance to oxidative stress (OS) in a growth assay under OS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…DNA-directed RNA polymerase Ⅱ, Spt20 family protein, and methyltransferase sirN-like protein, which are genes related to gene transcription regulation, were also upregulated. Recent studies have shown the modulation of pathogenesis and virulence by transcriptional factors of entomopathogenic fungi [ 70 , 71 , 72 ]. Regulation of activation of gene transcription can contribute to toxicity in the host [ 73 , 74 ], while the recQ family helicase is involved in DNA repair and replication [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…DNA-directed RNA polymerase Ⅱ, Spt20 family protein, and methyltransferase sirN-like protein, which are genes related to gene transcription regulation, were also upregulated. Recent studies have shown the modulation of pathogenesis and virulence by transcriptional factors of entomopathogenic fungi [ 70 , 71 , 72 ]. Regulation of activation of gene transcription can contribute to toxicity in the host [ 73 , 74 ], while the recQ family helicase is involved in DNA repair and replication [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…CDA gene mutants were constructed by homologous recombination as described previously ( 50 , 51 ). The specific fragment was cloned from the genome of the WT strain and was integrated into the appropriate position of E. coli ( Escherichia coli ) P0380 by using the corresponding endonucleases and ligases to generate gene deletion and complementation vectors.…”
Section: Methodsmentioning
confidence: 99%
“…The immersion and hemocoel injection methods were adopted to determine fungal virulence to G. mellonella ( 44 ). Specifically, a total of 30 larvae (∼300 mg each) were immersed in 30 ml of a conidial suspension (10 7 conidia/ml) for approximately 10 s or injected into the abdomen with 1 μl of conidial suspension (5 × 10 5 conidia/ml; 500 conidia per larva).…”
Section: Methodsmentioning
confidence: 99%